Effect of Butterfly Pea Flower (Clitoria ternatea L.) Gel on PDGF and IL-6 Expression in UVB-Exposed Wistar Rats - Pratiwi, Desy Elia; Wibowo, Joko Wahyu; Isradji, Israhanto (Poltekkes Kemenkes Banjarmasin Jurusan Analis Kesehatan, 2025)
Ultraviolet-B (UV-B) exposure can trigger inflammation and inhibit skin regeneration by decreasing Platelet-Derived Growth Factor (PDGF) and increasing Interleukin-6 (IL-6). Butterfly Pea (Clitoria ternatea L.) is known for its antioxidant and anti-inflammatory properties, but its effectiveness as a topical gel has not been widely studied. This study aims to evaluate the effect of Butterfly Pea (Clitoria ternatea L) extract gel on IL-6 and PDGF expression in Wistar rats exposed to UVB. This study is an in vivo experimental study with a post-test-only control group design. A total of 20 Wistar rats (200–250 g) were divided into four groups consisting of 5 rats per group: K1 (healthy control), K2 (gel base + UV-B), K3 (5% Clitoria ternatea gel + UV-B), and K4 (10% Clitoria ternatea gel + UV-B). UV-B exposure was carried out for 20 minutes/day (160 mJ/cm²) for 7 days. PDGF and IL-6 expression were analyzed by RT-qPCR. Statistical tests using Shapiro-Wilk, Levene, Kruskal-Wallis for PDGF expression, and One-Way ANOVA for IL-6 expression. Studies have shown that PDGF expression did not show significant differences between groups (p=0.455), with an average expression of K1: 1.39±0.62, K2: 1.39±0.61, K3: 1.66±0.87, and K4: 1.52±1.88. IL-6 expression was also similar (p=0.663), an average of K1: 1.02±0.18, K2: 1.11±0.33, K3: 1.22±0.23, and K4: 1.16±0.26. Conclusion: Administration of Clitoria ternatea L. extract gel did not have a significant effect on PDGF and IL-6 expression in the skin of Wistar rats exposed to UVB light. Both 5% and 10% doses showed no significant difference in the expression of the two markers; further studies with larger sample sizes, longer treatment durations, and improved topical delivery systems are needed. are recommended to better evaluate its therapeutic potential.